2005
DOI: 10.1007/s10384-004-0131-6
|View full text |Cite
|
Sign up to set email alerts
|

Myopia Control Trial with Progressive Addition Lenses in Japanese Schoolchildren: Baseline Measures of Refraction, Accommodation, and Heterophoria

Abstract: The measurements reported herein will serve as a basis for assessing changes that occur over a 3-year follow-up period. Compared with the baseline measurements in the Correction of Myopia Evaluation Trial, clear differences were observed in the mean cycloplegic autorefraction and distance prescriptions. The accommodation and heterophoria data showed characteristics similar to those recently reported in myopic children abroad.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 16 publications
(9 reference statements)
1
9
1
Order By: Relevance
“…In a school-based cohort study conducted in China, [39] myopia was reported to be, on average,-1.43 D and -2.58 D in 7- and 14-year-old Chinese children, respectively. Similar to a study by Hasebe et al in Japanese school children, [40] no significant correlation was found between refraction and age in our study.…”
Section: Discussionsupporting
confidence: 90%
“…In a school-based cohort study conducted in China, [39] myopia was reported to be, on average,-1.43 D and -2.58 D in 7- and 14-year-old Chinese children, respectively. Similar to a study by Hasebe et al in Japanese school children, [40] no significant correlation was found between refraction and age in our study.…”
Section: Discussionsupporting
confidence: 90%
“…This trial had been approved by the ethics panel of Okayama University in May 2002, and was carried out at Okayama University Hospital between 1 July 2002 and 30 July 2006. 20 The subjects had myopic refractive errors but no other ophthalmological disease. In conformity with the Helsinki Declaration, an adequate explanation of the study aim and methods was given to the children and their parents, who gave their written consent before the study.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-fi ve minutes after the second application, autorefraction and keratometry were performed with an ARK-2000 autorefractor/keratometer (Nidek, Gamagori, Japan). 20 The mean of fi ve readings was used as the representative measurement. All measurements were performed by a single ophthalmologist.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, using the data from a clinical trial that evaluates the treatment effects of progressive addition lenses (PALs) in myopia control, we tried to clarify the seasonal variations in Japanese children and compared the results with those reported in the US and China [4,5].…”
Section: Introductionmentioning
confidence: 97%